PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPHORA (Studi Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Siti Fatimah; Yustina Chrismardani (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This research aims to determine green marketing which consists of product, price, place and promotion on the decision to purchase Sephora products (Study of Trunojoyo Madura University Students) in 2017 to 2020. Sampling in this study used purposive sampling and analyzed using multiple linear regression analysis. The results of this study indicate that green marketing which consists of product, price, place and promotion on the decision to purchase Sephora products has a simultaneous effect on customer loyalty, and the product, price, place and promotion variables have a partial significant effect on customer loyalty.